Psychophysiological states of elite wrestlers after critical life events - Korobeynikov, G.; Kokun, O.; Korobeinikova, I.; Korobeinikova, L.; Raab, M. (International Journal of Wrestling Science, 2024)
The current stage of human development is characterized by the emergence of new risks and military conflicts. One of the large-scale ones is Russia's military aggression against Ukraine. Negative consequences of the war can be mental disorders and post-traumatic stress in the civilian population (Kokun et al., 2023; Rzonca et al., 2024). Some authors point to an increase in anxiety and distress among the population of Ukraine over the past two years (Kurapov et al., 2023; Predko et al., 2023). More than 500 Ukrainian athletes and coaches were killed from 24.02.2022. However, in the conditions of war, Ukrainian athletes continue to train and participate in competitions.